Meningkatkan Semangat Minat Belajar Al-Qur’an pada Anak di Panti Asuhan Al-Jami’yatul Washliyah - Liza Afilia Suryani; Husni Thamrin (Yayasan Literasi Sains Indonesia, 2022)
Interest in reading needs to be instilled and grown since children are small because interest in reading in children will not be formed by itself, but is strongly influenced by stimuli obtained from the child’s environment. Especially the interest in learning to read the Qur’an which is the main guideline for Muslims. Renewal in the world of education can be done by using technology in the sector supporting the learning process as an innovation in education. Several developed and developing countries utilize multimedia technology as a means of delivering learning materials. There are several roles of learning media, among others, learning will attract the attention of students so that it can lead to learning motivation and allow students to master learning objectives better. The purpose of this research is to increase the spirit of interest in learning the Qur’an in children at the Al-Jami’yatul Washliyah Orphanage. The intervention program is carried out using the Mezzo Intervention by Zastrow which consists of Engagement, Intake and Contract, Assessment, Planning, Intervention, Evaluation and Termination. The final results obtained are that children become more aware and understand in learning to read the Qur’an.